Pretreatment Neutrophil–Lymphocyte Ratio. Issue 11 (March 2015) - Gao, Fangyuan; Li, Xiaoshu; Geng, Mingfan; Ye, Xieqiong; Liu, Huimin; Liu, Yao; Wan, Gang; Wang, Xianbo; Yang., Hua
<x xml:space="preserve">Abstract</x> Abstract The neutrophil-to-lymphocyte ratio (NLR) has been shown to be associated with prognosis in various types of cancer. We evaluated pretreatment NLR as a predictor of poor prognosis in patients with hepatocellular carcinoma (HCC), and we compared the prognostic value of NLR with other prognostic scores. We retrospectively analyzed 825 patients diagnosed with HCC between October 2008 and May 2012. Baseline data, including the NLR and the Child–Pugh class or Model for End-Stage Liver Disease (MELD) score, were recorded before treatment. The relationships between overall survival (OS) and the study variables were assessed using univariate and multivariate analyses and receiver operating characteristic (ROC) curves. The prognostic value of NLR was assessed using a Kaplan–Meier survival analysis and compared with that of the Barcelona-Clinic Liver Cancer (BCLC) and Tumor, Node, Metastasis (TNM) staging. The NLR, γ-glutamyltranspeptidase, α-fetoprotein ≥400 ng/mL, tumor number ≥3, tumor size ≥5 cm, lymph node metastasis, portal vein involvement, and Child–Pugh class were significantly associated with OS. The NLR demonstrated the strongest prognostic value (area under ROC curve = 0.811). An NLR ≥2.7 was a significant predictor of poor OS (P < 0.0001), and the survival period of patients with an NLR ≥2.7 decreased with more advanced BCLC and TNM stage. Pretreatment NLR is a useful prognostic biomarker in HCC patients. The prognostic value of NLR ≥2.7 is superior to that of MELD stage or Child–Pugh class, and correlates with that of BCLC and TNM staging scores.